Pandangan Masyarakat Tentang Tradisi Dhempo’ dalam Proses Pertunangan (Studi Kasus di Desa Jarin Kecamatan Pademawu Kabupaten Pamekasan) - Amin, Fahrisal (Fakultas Syariah IAIN Madura, 2021)
(The focus of the problem studied in this study, namely: what are the reasons for the community of Jarin Village, Pademawu District, Pamekasan Regency to carry out the dhempo tradition? and what is the community's view of the dhemo' tradition in the engagement process in Jarin Village, Pademawu District, Pamekasan Regency? After doing the research, it was concluded that the strong reason for the community to conduct demonstrations was one of them on the basis of following the previous elders.)